Study on Pressure Distribution in the Blade Passage of the Francis Turbine - Sutikno, Djoko; Soenoko, Rudy; Pratikto, Pratikto; PT, Fery Putra; Nur Cahyo, Ponco Muchamad (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2011)
Pressure distribution along a series of guide and runner blade passages of the Francis turbine are useful to be known in order to predict flowing water pressure through the passages whether the pressure under the vapor pressure or not. Furthermore, when at any section of the passages the water pressure under the vapor pressure a cavitations will occur. In this study, the pressure of flowing water throughout the blade passages were measured at four sections along the passages by using four mercury deflection manometers and conditions of the flowing water were recorded by using a stroboscope and camera. The turbine was operated at 5 different heads with the same guide blade openings. Water pressures at the inlet and outlet turbine were measured by a Bourdon manometer of each. The flow rates were measured by using an orifice plate equipped with a mercury deep well manometer. The forces were measured by using a prony brake and turbine rotations were detected by using a digital tachometer. The result of the research state that head drop on the guide and runner blades, and turbine efficiency changing as the head, flow rate and turbine speed changed. The head drop on the runner was greater than that on the guide blade. Cavitations were not occoured because the lower pressure along the passages were still higher than vapor pressure. Water pressure decreased from the guide blade inlet to the runner outlet. Keywords : Francis turbine, Pressure distribution, guide and runner passages, head drop, cavitations, efficiency.